2015
DOI: 10.5539/ijef.v7n4p176
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Structure and Testing of Theories: A Study on the Listed Manufacturing Companies in Bangladesh

Abstract: The objectives of this study are to identify the significant determinants of capital structure of the listed manufacturing companies in Bangladesh and to test the relevant capital structure theories. This study used a panel dataset including 74 manufacturing companies listed under 8 industries in Dhaka Stock Exchange (DSE) for the period of 2002-2011. The Unit Root tests suggested that all series were stationary. Using Panel Corrected Standard Error Regression Model and Random Effects Tobit Regression Model, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 26 publications
6
51
1
2
Order By: Relevance
“…These are well-acknowledged proxies used for capital structure in almost all studies i.e. Hossain and Hossain (2014) …”
Section: Dependent Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…These are well-acknowledged proxies used for capital structure in almost all studies i.e. Hossain and Hossain (2014) …”
Section: Dependent Variablesmentioning
confidence: 99%
“…In Bangladesh, Hossain and Hossain (2014), using Panel Corrected Standard Error Regression Model and Random Effects Tobit Regression Model on a large panel dataset including 74 manufacturing companies listed under 8 industries in DSE for the period of 2002-2011, found that there is an inverse relationship between profitability and capital structure. They also claimed that growth rate, debt service coverage ratio, non-debt tax shield, financial costs, free cash flow to firm, agency costs and dividend payout ratio have negative relationship with capital structure whereas managerial ownership, on the contrary, has positive relationship with capital structure.…”
Section: Mixed Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCSEs model will correct the problems automatically and models will present reliable best estimates for our variables. Kmeta (1997) argued that PCSEs as an alternative to the Feasible Generalized Least Square (FGLS) for fitting the panel data models when the errors are not independent and identically distributed; rather the errors are either heteroskedastic across panels or heteroskedastic and contemporaneously correlated across panels, with or without autocorrelation (Hossain. I andHossain.…”
Section: Panels Corrected Standard Errors (Pcses) Regression Modelmentioning
confidence: 99%
“…The econometric regression model will produce spurious or non-sensible regression results relating to the relationship between dependent and independent variables when non-stationary data were employed in analysis. Non-stationary data this is when a data series does not have a constant mean variance and auto-covariance at various lags over time (Gujarati, 2007, Hossain. I and Hossain.…”
Section: Linearity Testmentioning
confidence: 99%